Development of a Military Character Education Model Based on the Values of Hubbul Wathan Minal Iman among Naval Academy Cadets at Bumi Moro Kerembangan, Surabaya - Hary Nurdi; Fahmi Hamdi; Salamah Salamah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
This study aims to develop a military character education model based on the values of Hubbul Wathan Minal Iman among Naval Academy cadets at Bumi Moro Kerembangan, Surabaya. The study is motivated by the importance of strengthening religious and nationalist character in shaping professional, disciplined, patriotic, and high-integrity Indonesian Naval officers amid the challenges of globalization and moral degradation among younger generations. The research employed a qualitative descriptive approach using Library Research methods. Data were collected through literature studies from scientific journals, books, academic articles, and relevant documents related to character education, military education, religious nationalism, and the concept of Hubbul Wathan Minal Iman. Data analysis was conducted using content analysis to examine and synthesize various theories and findings from previous studies. The findings indicate that the values of Hubbul Wathan Minal Iman are highly relevant to the development of cadets’ character through the integration of religiosity, nationalism, discipline, loyalty, and the spirit of defending the nation. An effective character education model can be implemented through curriculum integration, spiritual and mental development, exemplary leadership from instructors, academy culture, and disciplined daily habits among cadets. The novelty of this research lies in the development of a military character education model that integrates the concept of religious nationalism into the military education system at the Naval Academy as a strategy for strengthening morality, ideology, and patriotism among future Indonesian Naval officers